2016
DOI: 10.5535/arm.2016.40.4.647
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cardiac Rehabilitation Exercise Training on Cardiopulmonary Function in Ischemic Cardiomyopathy With Reduced Left Ventricular Ejection Fraction

Abstract: ObjectiveTo observe the effect and safety of cardiac rehabilitation (CR) exercise in ischemic cardiomyopathy and to compare the results between patients with preserved left ventricular ejection fraction (LVEF) and reduced LVEF.MethodsPatients with ischemic cardiomyopathy with LVEF <50% were included as subjects. The patients were classified into the preserved LVEF (pLVEF; LVEF 41%–49%) group and the reduced LVEF (rLVEF; LVEF ≤40%) group. Patients underwent hourly aerobic exercise training sessions with an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(42 reference statements)
0
10
0
1
Order By: Relevance
“…Although the importance of EBCR after an AMI is well established, several factors which pertain to its optimal application have not yet been fully ascertained [11, 12, 17]. Importantly, AMI survivors with a reduced ejection fraction (EF) represent a higher-risk subgroup [3] and in some series are referred less often for these programmes [8, 18, 19]. Additionally, the impact of EBCR across different ranges of EF has been the focus of heightened interest [8, 19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the importance of EBCR after an AMI is well established, several factors which pertain to its optimal application have not yet been fully ascertained [11, 12, 17]. Importantly, AMI survivors with a reduced ejection fraction (EF) represent a higher-risk subgroup [3] and in some series are referred less often for these programmes [8, 18, 19]. Additionally, the impact of EBCR across different ranges of EF has been the focus of heightened interest [8, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, AMI survivors with a reduced ejection fraction (EF) represent a higher-risk subgroup [3] and in some series are referred less often for these programmes [8, 18, 19]. Additionally, the impact of EBCR across different ranges of EF has been the focus of heightened interest [8, 19]. This stems from the fact that, although there are currently numerous parameters of potential interest in the prognostic assessment after an AMI, EF remains the most important parameter in terms of clinical decision-making and overall prognosis [3, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was based on rMSSD index [36] because it presents the highest sample number necessary for this study, compared with the other main variables [6 minutes walking test [37] and tumor necrosis factor (TNF)-alpha [38] ]. A standard deviation of 17 ms, alpha risk of 5%, and beta of 80% was considered for the calculus, which resulted in 44 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…In a cohort study, 37 patients (mean age, 66 years) with MI underwent a 5-week CR program, and the results indicated that cardiac rehabilitation improved QoL, exercise capacity, and autonomic modulation (Fallavollita et al, 2016). Kim et al suggested that a 6-week CR exercise program with an intensity of 60-85% heart rate reserve improved cardiopulmonary function in patients with ischemic cardiomyopathy (Kim et al, 2016). Patients with a home-based walking program showed an obvious improvement of functional capacity, increasing their inspiratory muscle endurance (PTHmax) and maximal inspiratory pressure (MIP) in 15 and 60 days following MI (Matos-Garcia et al, 2017).…”
Section: Cardiac Rehabilitation and MImentioning
confidence: 99%